Endorsing a Civic (vs. an Ethnic) Definition of Citizenship Predicts Higher Pro-minority and Lower Pro-majority Collective Action Intentions - Kende, Anna; Lantos, Nóra A.; Krekó, Péter (Frontiers in Psychology, 2018)
Europe has witnessed a polarization of intergroup attitudes and action tendencies in the context of the refugee crisis of 2015 and the rise of right-wing populism. Participation in both pro-minority collective action and right-wing nationalist movements has increased among members of ethnic majority groups. We analyzed these collective action intentions toward Roma people and Muslim immigrants in Hungary related to concepts of citizenship. In an online survey relying on a probabilistic sample that is demographically similar to the Hungarian population (N = 1069), we tested whether relying on the concept of ethnic citizenship predicted higher intentions to engage in pro-majority collective action, and lower intentions to engage in pro-minority collective action, and whether the connection was mediated by fear and empathy. We expected that the connections would be the opposite for civic citizenship. Our results supported the hypotheses, but we found that the ethnic definition was a stronger predictor of intergroup action intentions toward the immigrant group, and the civic definition a stronger predictor in case of the Roma minority group. Therefore, in a second study (N = 320) we collected experimental evidence to show that civic and ethnic citizenship affected both types of collective action tendencies. We found that the manipulation had an effect on the concept of citizenship only in the ethnic dimension, but nevertheless influenced pro-minority collective action intentions especially in the presence of high empathy and low fear in the expected direction, that is, pro-minority collective action intentions were higher in the civic citizenship condition than in the ethnic citizenship condition. The effect was not found with regard to pro-majority collective action intentions. These findings highlight the potential consequences of nationalist rhetoric on intergroup action intentions and point out both the scope and the limits of influencing its effect.